Epidemiological factors of septoria tritici blotch (Zymoseptoria tritici) in durum wheat (Triticum turgidum) in the highlands of Wollo, Ethiopia - Hailemariam, Bogale Nigir; Kidane, Yosef Gebrehawaryat; Ayalew, Amare (Springer, 2020)
Septoria tritici blotch (STB) (Zymoseptoria tritici) is a major disease of durum wheat, an economic crop grown in the highlands of Wollo in Ethiopia. To determine the status of this disease, we conducted surveys in five districts of Wollo (Meket, Woreilu, Wadila, Jama, and Dessie Zuria) during the 2015 cropping season. We visited 75 farm plots to determine the prevalence, incidence, and severity of STB. STB prevalence varied among locations, genotypes, planting dates, growth stages, previous crops, plant population, weed population, and soil types. Similarly, disease intensity also varied along all independent variables. The level of incidence was high in all the visited districts, and the level severity ranged from 9.9 to 59.3% while the incidence varied from 50 to 100%. The mean differences in incidence and severity within the districts’ variable classes, altitude, varieties, growth stage, plant population, planting date, previous crop, weed population, and soil type were high. The independent variables, districts, altitude, varieties, growth stage, plant population, planting date, previous crops, weed population, and soil type, were significantly associated with high incidence and severity of STB as single predictor in the logistic regression model. A reduced multiple variable model was fitted using districts, altitude, varieties, growth stage, plant population, planting date, previous crop, weed population, and soil type as independent variables. High incidence (> 50%) and severity (> 25%) had a high probability of association to all independent variables, except previous crop. Low disease incidence (≤ 50%) and low disease severity (≤ 25%) had high probability of association to the previous crop. Environmental variables, cultivation practice, and responses were important for the development of STB. Therefore, these factors must be considered in designing strategies for the effective management of STB.